Lifelong learning programme as a mechanism of change at the national level - Širok, Klemen (Managing global transitions, 2012)
European Commission (EC) funding programmes in the field of education and training present supranational policy instruments bringing change to various levels of social reality at the national level. In an attempt to present the holistic view of their effect, this paper presents the results of the Lifelong Learning Programme (LLP) impact evaluation, which consisted of a mixed method research approach combining a focus group discussion method, interviews, content analysis, and survey research. Results show that EC education and training funding programmes do bring change to the national (system), mezzo (organisational), and micro (individual) levels. Yet, the impact seems to be different at the observed levels as well as in the different target domains, and is weakest at the system level. This prompts the question about whether it makes much (economic) sense to exploit EC programmes as mechanisms of national policy goal implementation.
Keywords: družbene spremembe; programi EK; vpliv; evalvacija; izobraževanje; education